Role-based access control - Ferraiolo, David (Artech House computer security series., 2003)
Role-based access control (RBAC) is a security mechanism that can greatly lower the cost and complexity of security administration for large networked applications. RBAC simplifies security administration by using roles, hierarchies, and constraints to organize privileges. This book explains these components of RBAC, as well as how to support and administer RBAC in a networked environment and how to integrate it with existing infrastructure.